ANALISIS AKUISISI PENGETAHUAN DAN KETERAMPILAN WARTAWAN DENGAN MOTIVASI UNTUK MENDAPATKAN AKURASI BERITA DI HARIAN WASPADA DI NANGGROE ACEH DARUSSALAM - Ira Marisa; Agustian Budi Prasetya (Journal of Business Strategy and Execution, 2013)
This study aims to determine the effect of the acquisition of knowledge and skills acquisition on the motivation of journalists to obtain accuracy in the news as well as to seek the most dominant influence between independent variables and the dominant influence of the dimensions of the free which will then be used as improvements in an effort to improve the quality of news and the ability of journalists. This research was conducted using survey method. Samples were journalists Daily Alert in Aceh, with respondents as many as 42 people. Data were collected through a questionnaire which covers the instrument variable acquisition of knowledge, acquisition of skills and motivation to get accuracy in news. Data were obtained and analyzed using t-test and regression at a significance level of 0.05. Results of the study found that: a significant difference between the acquisition of knowledge and skills acquisition on the motivation to get the accuracy of the news. It was concluded that the knowledge and skills possessed by journalists to help them obtain information for the accuracy of the news. However, new skills more influential those journalists are motivated to apply the new skills they have to get accurate news.